2011
DOI: 10.1088/0004-637x/736/2/129
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of the Circumnuclear Starburst Ring in the Barred Galaxy NGC 1097

Abstract: We report high resolution 12 CO(J = 2-1), 13 CO(J = 2-1), and 12 CO(J = 3-2) imaging of the Seyfert 1/starburst ring galaxy NGC 1097 with the Submillimeter Array to study the physical and kinematic properties of the 1-kpc circumnuclear starburst ring. Individual star clusters as detected in the HST map of Paα line emission have been used to determine the star formation rate, and are compared with the properties of the molecular gas. The molecular ring has been resolved into individual clumps at GMA-scale of 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
96
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(111 citation statements)
references
References 70 publications
(87 reference statements)
15
96
0
Order By: Relevance
“…For NGC 1365, Sakamoto et al (2007) found five CO hot spots with line widths (FWHM) between 60 and 90 km s −1 that seem to be associated with SSCs of ∼10 6 M (Galliano et al 2005). Hsieh et al (2011) found many GMAs in the molecular ring (14 GMAs) and the dust lane (5 GMAs) of NGC 1097. They subdivided the GMAs in the molecular ring into two categories: GMAs with broad (σ > 30 km s −1 ) and narrow (σ < 30 km s −1 ) line dispersions.…”
Section: Gmas In Galaxies With Nuclear Molecular Ringsmentioning
confidence: 97%
See 3 more Smart Citations
“…For NGC 1365, Sakamoto et al (2007) found five CO hot spots with line widths (FWHM) between 60 and 90 km s −1 that seem to be associated with SSCs of ∼10 6 M (Galliano et al 2005). Hsieh et al (2011) found many GMAs in the molecular ring (14 GMAs) and the dust lane (5 GMAs) of NGC 1097. They subdivided the GMAs in the molecular ring into two categories: GMAs with broad (σ > 30 km s −1 ) and narrow (σ < 30 km s −1 ) line dispersions.…”
Section: Gmas In Galaxies With Nuclear Molecular Ringsmentioning
confidence: 97%
“…These barred spirals are so-called twin-peak galaxies because they contain nuclear molecular rings that show a double-peak structure in their molecular gas distribution perpendicular to the stellar bar, where the starburst ring and the dust lanes connect (Sakamoto et al 2007;Hsieh et al 2011). NGC 1614 harbors an asymmetric ring and displays at least one connection point with its dust lanes.…”
Section: Comparing Ngc 1614 With Galaxies With Nuclear Molecular Ringsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of two velocity components is what is expected from the region being a convergent area of two types of gas orbits. Such double-peak line profiles have been observed in the x 1 -x 2 orbit-crowding regions of a number of barred galaxies (e.g., Regan et al 1999;Sakamoto et al 2007;Hsieh et al 2011).…”
Section: M83mentioning
confidence: 69%